CURRENT STATE OF THE PROBLEM OF FORMATION CULTURES OF COMMUNICATION OF THE FUTURE TEACHERS BY DIALOGICAL MEANS LEARNING SITUATIONS (Pedagogy of Higher and Secondary Education, 2004)
The article deals with the various problems and aspects of communicational culture formation in dialogue training studying situation of professional orientation.